2018
DOI: 10.1007/s10803-018-3516-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences During Toddlerhood in Autism Spectrum Disorder: A Prospective Community-Based Longitudinal Follow-Up Study

Abstract: Relatively few studies have examined gender differences in infants and toddlers, and most focus on clinically referred samples or high-risk infant cohorts. The current study aimed to examine gender differences in early autism manifestations and cognitive development in a community-ascertained sample. In total, 46 males and 21 females with ASD were seen at approximately 24 and 48 months of age. No significant gender differences were observed on overall cognitive ability, verbal skills, non-verbal skills, overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 66 publications
2
12
1
Order By: Relevance
“…An item-by-item analysis revealed that boys showed more elevated symptoms, especially in the social communication domain. This is consistent with a previous study with toddlers and young children that found more elevated social communication symptoms in girls than in boys [ 66 ]. Similarly, Little, Wallisch, Salley, & Jamison [ 67 ], who studied early parental concerns regarding their child’s development, found that parents of boys diagnosed later with ASD reported more concerns regarding social interaction compared with girls with ASD or children with other developmental disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…An item-by-item analysis revealed that boys showed more elevated symptoms, especially in the social communication domain. This is consistent with a previous study with toddlers and young children that found more elevated social communication symptoms in girls than in boys [ 66 ]. Similarly, Little, Wallisch, Salley, & Jamison [ 67 ], who studied early parental concerns regarding their child’s development, found that parents of boys diagnosed later with ASD reported more concerns regarding social interaction compared with girls with ASD or children with other developmental disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…At the degree level, female ASC individuals have more attention preference for social stimuli (Chawarska et al, 2016) and less social communication impairment than males (Hartley and Sikora, 2009; Zwaigenbaum et al, 2012). However, neither gender differences in structure nor gender differences in degree are absolute; they are affected by a series of other factors, such as sample size and age (Lawson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that (COX)‐2 − mice can have sex‐ and age‐specific social abnormalities, which have also been reported in human cases of ASD. For example, a recent study by Lawson et al found that females with ASD exhibited more social impairments compared with matched males. Females with Smith‐Magenis syndrome, a complex genetic neurodevelopmental syndrome with autism features, also display a greater number of abnormal social symptoms …”
Section: Discussionmentioning
confidence: 99%